PENGENALAN PRODUK BUDAYA MELALUI SEJARAH JATIDIRI BANGSA: Studi Kasus Kesadaran Sejarah di SMA Labschool Kebayoran - Donny Satryo Wibowo; Kurniawati Kurniawati (Universitas Trisakti, 2020)
AbstractKnowledge of cultural products is one of the basic assets of advancing the nation with highcivilization and its works that are recognized by the world, and is closely related to identity, andcan be explored through historical consciousness. According to experts, historical consciousnesscannot be separated from culture and identity. Historical consciousness is the cognition of anindividual or a group of people and involves cultural awareness of a relationship between thepast and the present, which helps to understand the future. Senior High School becomes likea gate for students to choose their way of life in the future in helping to build the nation andits country’s defense. Going to high school is not just a prerequisite for entering tertiary levelor a requirement for being called an adult and being able to go directly into the real world insociety, but also a stage of learning that is expected to explore the potential of ethnic culturalidentity, can also harmoniously develop the potential of national identity as Indonesian nation,to advance this nation to achieve its glory. Research with this case study approach gets severalfindings related to the historical awareness of high school students including the potentialawareness of the historical identity of their identity for the advancement of future developmentwith the character and wealth of Indonesia. Abstrak Pengenalan pada produk budaya adalah salah satu modal dasar memajukan bangsadengan peradaban tinggi dan karya-karyanya yang diakui dunia, dan berhubunganerat dengan identitas jatidiri, serta dapat digali melalui kesadaran sejarah. Kesadaransejarah menurut para ahli tidak dapat dipisahkan dari kebudayaan dan idenitas jatidiri. Kesadaran sejarah adalah kognisi dari individu atau sekumpulan masyarakatdan melibatkan kesadaran budaya atas suatu hubungan antara masa lalu denganmasa kini, yang membantu untuk memahami masa depan. Sekolah Menengah Atasmenjadi seperti gerbang dari para siswa untuk memilih jalan hidupnya ke depandalam turut membangun bangsa beserta ketahanan negaranya. Bersekolah SMAtidak sekedar hanya sebagai syarat untuk memasuki tingkat perguruan tinggi atausyarat untuk disebut dewasa dan dapat terjun langsung ke dunia nyata di masyarakat,namun juga merupakan kancah tahap pembelajaran yang diharapkan dapatmenggali potensi identitas budaya etnisnya, juga dapat harmonis mengembangkanpotensi identitas nasionalnya sebagai bangsa indonesia, untuk memajukan bangsa inimencapai kejayaannya. Penelitian dengan pendekatan studi kasus ini mendapatkanbeberapa temuan terkait kesadaran sejarah siswa SMA antara lain adalah potensi kesadaran sejarah identitas jatidiri mereka untuk pemajuan pembangunan di masadepan dengan karakter dan kekayaan yang dimiliki Indonesia.